Geomarketing : methods and strategies in spatial marketing - Cliquet, Gérard,Ed (Geographical information systems series, 2006)
This title describes the state of the art in all areas of spatial marketing, discussing the various constituents which make up the geography of markets. Demand varies according to location and can be measured according to revenue, the number of households, spending patterns and lifestyles